HUMAN RESOURCES DEVELOPMENT STRATEGY IMPROVE PERSONNEL PERFORMANCE USING SWOT ANALYSIS METHOD - Andry Kuswoyo; Okol Sri Suharyo; Zainal Syahlan (STTAL POSTGRADUATE - INTERNATIONAL CONFERENCE, 2021)
In the era of globalization, the development of the security, economic and political situation is very dynamic which is marked by the existence of very open and tight competition. In these conditions an organization is required to be able to make adjustments in various aspects that exist within the organization, especially the organization. This study aims to determine the strategy of developing human resources by analyzing the strengths, weaknesses, opportunities and threats they have. The research method used is the SWOT Matrix Qualitative Method, IFAS Table, EFAS. From the calculation of the IFAS table the strength is lower than the weakness, and the calculation from the EFAS table is greater than the threat so that the diagram point is at point 1 and stability 1. The strategy used is the right strategy that must be applied by the Office of personnel based on SWOT ANALYSIS, namely by applying the SO Strategy (Strength - Opportunities), namely to utilize the strengths of the organization to capture the opportunities of existing organizations. Keywords: HR Development Strategy, SWOT Analysis, IFAS, EFAS